Agriculture and intellectual property rights: economic, institutional and implementation issues in biotechnology - Santaniello, V (Agriculture and intellectual property rights: economic, institutional and implementation issues in biotechnology, 2000)
This book presents the perspectives of policy-makers and economists on a highly topical subject. Plant breeding patents, the ownership of biological innovation and associated intellectual property rights (IPR) are the subject of increased attention worldwide. They are particularly relevant in the field of agricultural biotechnology, but until recently evoked little policy analysis. IPRs are particularly relevant in the field of agricultural biotechnology. They are issues affecting public and private sector organizations and companies, and are significant for developing as well as developed countries.